One-step patterning of arbitrary-shaped diffractive micro-optics on thin-film graphene oxides - Lim, Joel Chin Huat (2018)
We present a methodology and instrumentation scheme for patterning of diffractive optical elements (DOE) on graphene oxide (GO) thin-film. The proposed is based on direct laser writing (DLW) process using a femtosecond (Fs) pulse laser as the energy source. GO is a thin film of graphite that has traditionally acted as a precursor for graphene but progressively gaining interest due to its unique optical properties. GO is transparent in its original state and will turn into reduced graphene oxides (rGO), which is opaque, after the laser photo-reduction. This unique transition characteristic enables the formation of DOEs such as diffraction grating, and Fresnel lens with sub-micrometer resolution. The automation control of laser and optomechanical element allow one-step direct printing of arbitrary shaped patterns on graphene oxides. We believe that this proposed fabrication process and arbitrary patterning capability of the Fs laser direct writing will provide a distinctive advantage in terms of thickness, compactness, and cost-effectiveness.